2009
DOI: 10.1111/j.1440-1746.2009.05854.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptors and their role in gastrointestinal disease

Abstract: The innate immune response to invading pathogens is centred upon a family of non-clonal, germline-encoded pattern recognition receptors (PRRs), the Toll-like receptors (TLRs). These provide specificity for a vast range of microbial pathogens, and offer an immediate anti-microbial response system. Thirteen mammalian TLRs have been described; 10 are expressed in humans, each responsible for the recognition of distinct, invariant microbial structures originating from bacteria, viruses, fungi and protozoa. The two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 121 publications
(132 reference statements)
0
110
0
5
Order By: Relevance
“…Unraveling these signaling cascades not only is vital for the understanding of the innate immune system in general, but also could help to identify new targets for immunomodulation (3,30). Furthermore, the consistency of the biological synergistic interactions between several combinations of PRRs may be important to the field of vaccine adjuvant research (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unraveling these signaling cascades not only is vital for the understanding of the innate immune system in general, but also could help to identify new targets for immunomodulation (3,30). Furthermore, the consistency of the biological synergistic interactions between several combinations of PRRs may be important to the field of vaccine adjuvant research (18).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these receptors can provide highly specific recognition of a vast range of microbes (3). Recognition of a PAMP by a PRR results in the activation of the innate immune system via several intracellular signaling pathways that are described in more detail elsewhere (4)(5)(6).…”
mentioning
confidence: 99%
“…With the methionine and choline deficient diet (MCDD) mouse model for NASH, Rivera et al observed portal endotoxemia and elevated expression of Toll-like receptor 4, CD14 and MD2 in Kupffer cells (58). These genes are key components of the LPS/TLR4 signaling pathway leading to the production of pro-inflammatory cytokines (59). One mechanism for hepatic exposure to endotoxin is increased gut permeability such as colitis or celiac disease.…”
Section: Possible Roles Of Lps In Metabolic Diseases and Nafld/nash: mentioning
confidence: 99%
“…78 NLRs are other important membrane-bound receptors besides the TLRs for the detection of proteins. More than twenty NLRs have been known till date, although the best characterized are NOD1 and NOD2.…”
Section: Gut Microbiota and Inflammationmentioning
confidence: 99%